2012
DOI: 10.2478/v10034-012-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary microRNA Analysis of non Syndromic Thoracic Aortic Aneurysms

Abstract: The development of thoracic aortic aneurysms (TAAs) involves a multifactorial process resulting in alterations of the structure and composition of the extracellular matrix (ECM). Recently, modifications in microRNA (miRNA) expression were implicated in the pathogenesis of TAA.This study presents a preliminary miRNA microarray analysis conducted on pooled ascending aorta RNAs obtained from non familial non syndromic TAA patients (five males and five females) compared to matched control pools. Ninety-nine differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 19 publications
7
27
0
Order By: Relevance
“…Additionally, the chord graph in Figure 6B shows the association of 18 genes with the top 8 GO terms. Interestingly, these results are similar to gene expression profiling of human TAA tissues where focal adhesion and adherens junction pathways were implicated (54,55). Accordingly, the observed differences in gene expression in the Notch1.129S6…”
Section: ;Fbn1supporting
confidence: 82%
“…Additionally, the chord graph in Figure 6B shows the association of 18 genes with the top 8 GO terms. Interestingly, these results are similar to gene expression profiling of human TAA tissues where focal adhesion and adherens junction pathways were implicated (54,55). Accordingly, the observed differences in gene expression in the Notch1.129S6…”
Section: ;Fbn1supporting
confidence: 82%
“…On the other hand hsa-miR-133b was not detected neither in plasma or tissue samples. These miRNAs were previously identified in the majority of the studies via microarray analysis (Liao et al 2011, Pahl et al 2012, Patuzzo et al 2012, Kim et al 2014, Wang et al 2015, Zhang et al 2015 and the fact that they were mainly detected in tissue samples may suggest that the quantity of these miRNAs in plasma is significantly low and possibly they cannot be detected with the RT-PCR method. For the remaining nine, the expression was lower in BB samples than BA samples.…”
Section: Discussionmentioning
confidence: 97%
“…From these studies only two did not report the clinical characteristics of the control groups (Maegdefessel et al 2012a(Maegdefessel et al , 2012b) and in Maegdefessel et al (2014), even though the clinical characteristics were reported for control plasma samples, they were not reported for control tissue samples. In addition, cases and control groups were age and gender matched in 16 studies (Boon et al 2011, Jones et al 2011, Liao et al 2011, Kin et al 2012, Pahl et al 2012, Patuzzo et al 2012, Biros et al 2014, Ikonomidis et al 2013, Zampetaki et al 2014, Chan et al 2015, Pei et al 2015, Wang et al 2015, Zhang et al 2015, Busch et al 2016, Licholai et al 2016, Wu et al 2016. For three studies we could not determine whether the gender of cases and control groups for tissue samples match since the gender was not clearly stated for the control groups (Maegdefessel et al 2012a(Maegdefessel et al , 2012b(Maegdefessel et al , 2014.…”
Section: Search Outcomementioning
confidence: 99%
See 2 more Smart Citations